A perovskite oxide with a tunable pore-size derived from a general salt-template strategy as a highly efficient electrocatalyst for the oxygen evolution reaction. Issue 17 (6th February 2019) - Yu, Haoran; Chu, Fuqiang; Zhou, Xiao; Ji, Junling; Liu, Yang; Bu, Yunfei; Kong, Yong; Tao, Yongxin; Li, Yongxin; Qin, Yong
Abstract : A porous perovskite oxide is fabricated by an inorganic salt-template strategy, which exhibits remarkable performance for the oxygen evolution reaction. Abstract : The fabrication of a perovskite oxide with a tunable pore-size was implemented by a general inorganic salt-template strategy. As a proof-of-concept, hierarchically porous PrBa0.5 Sr0.5 Co1.5 -Fe0.5 O5+ δ (PBSCF) with a surface area of 148 m 2 g −1 was successfully prepared, which exhibited remarkable electrocatalytic performance for the oxygen evolution reaction.